The Influence of the Problem Based Learning Model on Student Interest and Learning Outcomes - Priskilla Ginting; Jamalum Purba (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
This research aims to (1) determine the effect of using the Problem Based Learning model on student learning outcomes in reaction rate material (2) knowing the effect of using models Problem Based Learning on students' learning interest in reaction rate material. The population of this study were all students of class XI MIPA SMAN 14 Medan. The sampling technique was carried out random sampling, namely class XI MIPA 3 as an experimental class with 34 students. The results obtained are the average value of the experimental data class pretest and posttest is 37.50 and 79.85, which means it is higher than the minimum completeness criteria (KKM) value, namely 75. Data from the normality and homogeneity tests obtained normal distribution and homogeneous data. The results of the hypothesis test were carried out using one sample t-test at the significance level α = 0.05, earned value tcount 2.403 > ttable 1.692 with sig. (2 tailed) 0.022 < α = 0.05 so Ha is accepted and H0 is rejected. Students' interest in learning in the experimental class obtained an average score of 77.02 with high criteria of 47.1% and medium criteria of 52.9%.